2022
DOI: 10.3390/agronomy12112724
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Resistance to Acetyl-CoA Carboxylase-Inhibiting Herbicide Cyhalofop-Butyl in a Chinese Echinochloa crus-galli Population

Abstract: A population of Echinochloa crus-galli (L.) P. Beauv obtained from direct-seeding rice fields in Jiangxi Province, China, exhibited high resistance levels (13.5-fold) to the acetyl-CoA carboxylase (ACCase)-inhibiting herbicide cyhalofop-butyl. Compared with the susceptible (S) population, this resistant (R) population evolved a cross-resistance to aryloxyphenoxypropionates (APPs) herbicides metamifop (2.9-fold) and fenoxapro-p-ethyl (4.1-fold), cyclohexanediones (CHDs) herbicide clethodim (4.7-fold), phenyl py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…With the extensive application of herbicides, multiple herbicide-resistant weed populations have been increasing rapidly in the past decade, which has been reported in E. phyllopogon, 24 E. crus-galli, 25,26 Eleusine indica, 27 L. rigidum, 28 and so on. The fast increase of MHR weeds would seriously S7.…”
Section: Discussionmentioning
confidence: 99%
“…With the extensive application of herbicides, multiple herbicide-resistant weed populations have been increasing rapidly in the past decade, which has been reported in E. phyllopogon, 24 E. crus-galli, 25,26 Eleusine indica, 27 L. rigidum, 28 and so on. The fast increase of MHR weeds would seriously S7.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, ACCase inhibitors, cyhalofop-butyl and metamifop, were the common herbicides to control this noxious weed in rice fields. It is no surprise that ACCase-inhibitor-resistant grass weeds, including L. chinensis, 6,22−24 E. crus-galli, 26,27 D. fusca, 25 and E. indica, 30 have frequently occurred in rice fields as a result of persistent herbicide use. In this study, we identified that one D. ciliaris var.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the cyhalofop-butyl- 25 In our previous study, E. crus-galli populations collected from Ningxia and Jiangxi provinces were found to evolve resistance to cyhalofop-butyl and metamifop. 26,27 In recent years, the farmers generally report that metamifop and cyhalofop-butyl have poor control effect on D. ciliaris var. chrysoblephara in seed-directing rice fields in Jiangsu and Anhui provinces of China.…”
Section: Introductionmentioning
confidence: 99%
“…For glyphosate, it was not possible to adjust to the model proposed by Streibig (1988). Thus, data were submitted to regression analysis (P < 0.05) using a four-parameter nonlinear logistic model (Seefeldt et al 1995), as used in other studies (Wu et al 2022; Yang et al 2022): …”
Section: Methodsmentioning
confidence: 99%